Keys to Business Performance: Improving Product Quality and Implementing Total Quality Management in Manufacturing - Nainggolan, Elisabeth; Cecilia; Sri Rezeki (LPPM STIE EKA PRASETYA, 2024)
In the current era of globalization, there is intense competition among companies so that these companies compete in meeting the needs and demands of their customers. To be able to meet customer demand, the company must be able to improve product quality and quality control or total quality management in the company so as to improve company performance and meet customer demand. The purpose of this study is to determine whether there is an effect of product quality and total quality management on business performance. The object of this research is the customers of PT. Budi Tamora Permai which consists of companies that buy semi-finished products which are then processed in the form of finished materials. The sampling technique used is saturated sampling where all members of the population are used as research samples and the data collection method in this study uses Quantitative methods by distributing questionnaires to respondents measured on a Likert scale. The results show that there is an effect of product quality and total quality management on business performance